Characterizing phenol mass transfer coefficients of composite extractive membranes with different PDMS thicknesses by electrochemical impedance spectroscopy. (October 2022) - Yao, Lei; Cheng, Qisong; Long, Ziyi; Chen, Zhe; Lin, Zhidong; Li, Yong; Tian, Yuxiao; Liao, Yuan
Abstract: The extractive membrane is typically composed of a selective layer prepared by polydimethysiloxane (PDMS) and a highly porous substrate. A thin and defect-free PDMS selective layer is critical for the extractive membrane. The extractive membrane performance is predominantly evaluated by its organic mass transfer efficiency, which needs to conduct a time-consuming aqueous-aqueous extractive test. Herein, we proposed a novel, rapid, and sensitive method to characterize the organic mass transfer efficiency of extractive membranes. In this paper, PDMS-coated nanofibrous composite membranes with controllable thickness were prepared by electrospinning. The mass transfer efficiency of as-developed membranes was characterized by electrochemical impedance spectroscopy (EIS). A straightforward relationship between the membrane impedance, the thickness of selective layer and the mass transfer rate of phenol was obtained. A theoretical equation suggesting a linear relationship between the transfer efficiency and membrane resistance was proposed, which was confirmed by the experimental data. Moreover, aniline, as another contaminant was selected to validate the effectiveness and universality of this method. Therefore, EIS can be promisingly utilized for valid predication of the organic mass transfer performances of extractive membranes without time-consuming running of extraction experiments. Graphical abstract: Unlabelled Image Highlights: Composite extractive membranes were fabricated via electrospinning. Extractive membranes with controlled PDMS layer thickness were measured by EIS. Impedance spectra were fitted with equivalent circuits. A linear relation between PDMS thickness and R m from EIS analysis was constructed. Overall mass transfer coefficient for phenol followed an inverse proportion to R m .